Application of Linear Programming for developing Distribution Optimization Model for Services: A Case Study of Hospital Speciality Services Distribution - Ghosh, Devi Prasad (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
The objective of the paper was to extend the tangible goods distribution model to services and develop a decision making tool that services distribution company such as hospital chain could use to derive a more efficient and effective distribution of scarce and expensive resources of specialists to its hospitals. The paper attempts to optimize the creation of speciality services infrastructure at a hospital location and planning for specialists resources. The paper developed the problem definition, the formulation of Linear Programming Model, the procedure is designed as a solution to the problem, and the outcome as benefits to the company is presented. Linear programming model is formulated that can be solved using commercial software. This paper demonstrates the potential for using linear programming in managing large-scale distribution problems for services. The model resulted in the creation of new metrics for measuring the performance for services distribution, the model will help the company understand conditions that results in hospital specialty services shortages, and the model lead to the discovery of inefficiencies in company speciality services distribution strategy. The model is directly beneficial to any company in hospital services distribution particularly speciality or super-speciality services. With a large proportion of speciality services sales is accounted by referral of physicians direct to customers, the distribution of speciality procedure services not only defines the cost but also customer satisfaction by managing services delivery quality & time and return-of-patients for post procedure check-ups. The model is also applicable for cases in any other services industries which operates in multiple markets and have large variety of Services Units.